Caught Between Techno-Science and Global Capitalism: Images of Global Warming. - James, Paul (Social Alternatives)
The article presents comments of the author on the image of global ecology. According to the author, ecology has become a division of economics. The merger of the disciplines of ecology and economics is part of the larger late-twentieth century trend towards a merger between techno-science and capitalism. With the maturing of the idea of global ecology, the entire planet becomes the object of an experiment in which the global ecosystem must be regulated to sustain its resources.